Work Place Stress with in Employees - Dr. Jitendra Singh, Dr. Chandra Prakash Verma, Prerna Yadav (Drugs and Cell Therapies in Hematology, 2021)
Stress is psychological and directly related to job. Job stress refers to a situations. Stress can be reduced if individual knows that who are stressor&how to cope with it. Occupational stress overrides when employees do not feel co-operationsfrom supervisors or co-workers & they feel that they do not have control over the task they are assigned . Work place stress is a concern for both employees and employers because stressful job conditions are related to employees’ well-being, physically and directed related to his performance . A study conducted by the WHO by International Labor Organization and found that when worker is utilized for long working hours, will lead to increased psycho-social occupational stress, and risk factor with the largest attributable burden of disease, according to these official estimates causing an estimated 745,000 workers to die from ischemic heart disease and stroke events in every year .